Astraeus – III. The environment and physical properties of reionization sources. Issue 1 (10th May 2021) - Hutter, Anne; Dayal, Pratika; Legrand, Laurent; Gottlöber, Stefan; Yepes, Gustavo
ABSTRACT: In this work, we use the astraeus (seminumerical rAdiative tranSfer coupling of galaxy formaTion and Reionization in N -body dArk mattEr simUlationS) framework that couples galaxy formation and reionization in the first billion years. Exploring a number of models for reionization feedback and the escape fraction of ionizing radiation from the galactic environment ( f esc ), we quantify how the contribution of star-forming galaxies (with halo masses $M_ h\gt 10^{8.2}\, {\rm \rm M_\odot }$ ) to reionization depends on the radiative feedback model, f esc, and the environmental overdensity. Our key findings are: (i) for constant f esc models, intermediate-mass galaxies (with halo masses of $M_ h\simeq 10^{9-11}\, {\rm \rm M_\odot }$ and absolute UV magnitudes of MUV ∼ −15 to −20) in intermediate-density regions (with overdensity log10 (1 + δ) ∼ 0−0.8 on a 2 comoving Mpc spatial scale) drive reionization; (ii) scenarios where f esc increases with decreasing halo mass shift, the galaxy population driving reionization to lower mass galaxies ($M_ h\lesssim 10^{9.5}\, {\rm \rm M_\odot }$ ) with lower luminosities ( MUV ≳ −16) and overdensities [log10 (1 + δ) ∼ 0−0.5 on a 2 comoving Mpc spatial scale]; (iii) reionization imprints its topology on the ionizing emissivity of low-mass galaxies ($M_h\lesssim 10^{9}\, {\rm \rm M_\odot }$ ] through radiative feedback. Low-mass galaxies experience a stronger suppression of star formation by radiative feedback and show lower ionizing emissivities in overdense regions; (iv) a change in f esc with galaxy properties has the largest impact on the sources of reionization and their detectability, with the radiative feedback strength and environmental overdensity playing a sub-dominant role; (v) James Webb Space Telescope -surveys (with a limiting magnitude of MUV = −16) will be able to detect the galaxies providing ${\sim}60{-}70{{\ \rm per\ cent}}$ (${\sim}10{{\ \rm per\ cent}}$ ) of reionization photons at z = 7 for constant f esc models (scenarios where f esc increases with decreasing halo mass).